Growth and Optical Properties of Large-Sized NaVO2(IO3)2(H2O) Crystals for Second-Harmonic Generation Applications - Xu, Xiang; Li, Bing-Xuan; Huang, Ling-Xiong; Yang, Bing-Ping; Zhang, Ge; Mao, Jiang-Gao (Inorganic chemistry, 2023)
Large-sized crystals of the quaternary iodate NaVO2(IO3)2(H2O) (NVIO) with centimeter-scale dimensions (23 mm × 18 mm × 6 mm as a representative) have been successfully grown by the top-seeded hydrothermal method. Linear optical properties have been measured, including the optical transmission spectrum and refractive index. The NVIO crystal possesses an optical window with high transmittance (above 80%) over the range of 500–1410 nm and exhibits strong optical anisotropy with large birefringence Δn (nz – nx ) of 0.1522 at 1064 nm and 0.1720 at 532 nm. Based on the measured refractive indices, the phase-matching conditions for second-harmonic generation (SHG) have been calculated, and SHG devices have further been fabricated along the calculated type I and type II phase-matching directions of (θ = 39.0°, φ = 3.8°) and (θ =53.8°, φ = 1.3°). Laser experiments of extra-cavity frequency doubling have been performed on these NVIO devices. It has been confirmed that the effective SHG conversion from 1064 to 532 nm could be achieved with an energy conversion efficiency of 8.1%. Our work demonstrates that large-sized NVIO crystals are promising in the frequency-doubling application.